Potret Pembelajaran Pendidikan Jasmani dan Aktivitas Fisik Siswa di Pondok Pesantren melalui Program Asistensi Mengajar - Wening Nugraheni; Firman Septiadi; Bachtiar; Titis Nurina; Pasaribu Ahmad Muchlisin Natas (Attractive : Innovative Education Journal, 2025)
Physical activity is essential for students' physical fitness, motor development, and learning readiness. However, Islamic boarding schools (pesantren) prioritize academic and religious routines, leaving limited time for structured physical activity. This study aims to describe the condition of physical activity and Physical Education learning in pesantren through a teaching assistance program initiated by university lecturers and pre-service teachers. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation at Pondok Pesantren Daruttaubah, West Java. The subjects included junior and senior high school students, PE teachers, and teaching assistants. The findings reveal that students' physical activity remains suboptimal due to dense schedules and limited facilities. Nevertheless, the teaching assistance program contributed positively by introducing adaptive learning strategies, game-based methods, and simple media that increased student engagement and motivation. Collaboration between universities, pesantren, and PE teachers created a more dynamic and contextual learning environment. This study identifies six priority areas for future research: (1) longitudinal experimental studies to examine causal effects; (2) development of an Islamic-integrated PE curriculum; (3) comparative studies across pesantren typologies (salaf, modern, convergence) and countries (Indonesia, Malaysia, Brunei, Southern Thailand); (4) exploration of psychological and sociocultural barriers; (5) digital transformation of PE in pesantren; and (6) sport policy analysis within the Ministry of Religious Affairs. These agendas are essential to strengthen evidence-based practices and policy advocacy. In conclusion, teaching assistance programs represent a strategic, collaborative model for improving the quality of Physical Education in Islamic boarding schools.